2022
DOI: 10.5195/ijt.2022.6456
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients With Heart Failure Assisted By Telerehabilitation: A Systematic Review and Meta-Analysis

Abstract: Introduction: Heart failure (HF) is a syndrome that implies several physical and emotional changes that compromise quality of life. Telerehabilitation is a strategy developed with the aim of involving and motivating cardiac patients to participate in cardiac rehabilitation in their daily routine at home. Objective: To review the impact of telerehabilitation on the quality of life of patients with HF. Methods: This is a systematic review using the PICO strategy, with a search conducted in the electronic data so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The home-based cardiac telerehabilitation increases cardio-respiratory fitness in patients suffering from coronary heart disease [ 22 ]. Telerehabilitation can improve the quality of life of heart failure patients by increasing mental, social, and sexual functions along with an increase in exercise capacity and reduction of symptoms, thus helping in regaining independence in carrying out activities of daily living [ 23 ].…”
Section: Editorialmentioning
confidence: 99%
“…The home-based cardiac telerehabilitation increases cardio-respiratory fitness in patients suffering from coronary heart disease [ 22 ]. Telerehabilitation can improve the quality of life of heart failure patients by increasing mental, social, and sexual functions along with an increase in exercise capacity and reduction of symptoms, thus helping in regaining independence in carrying out activities of daily living [ 23 ].…”
Section: Editorialmentioning
confidence: 99%
“…The study offered: HF patient education before hospital discharge, regularly scheduled telephone coaching, and home telemonitoring of symptoms ( Ong et al, 2016 ). Individuals participating in the intervention experienced improvements in their quality of life over the course of the study ( Cordeiro et al, 2022 ). Research has shown that telephone contact to a trained nurse with access to a family physician, can prevent hospitalization in a quarter of HF patients ( Kolasa et al, 2020 ).…”
Section: Real-time Interactive Servicesmentioning
confidence: 99%
“…Heart Failure (HF) is a global burden and a life-threatening disease, affecting over 60 million people worldwide, a survival-rate at approximately 35 %, and an increasing prevalence with age [ 1 , 2 ]. HF is associated with high healthcare costs and is a growing burden within the healthcare sector.…”
Section: Introductionmentioning
confidence: 99%
“…As a part of treating HF, cardiac rehabilitation (CR) plays an important role, as it aims to improve recovery through setting up programs and offering advice for patient's physical activity, diet disease management, and control of risk-factors associated with HF [ 3 , 4 ]. The major HF risk-factors include diabetes, high blood pressure, smoking, and obesity [ 1 ]. Furthermore, CR aims to improve recovery by enhancing the health-related quality of life in patients, which may be assessed using various quality of life surveys and questionnaires [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation